Maternal depression and anxiety symptoms across pregnancy and the postnatal period: Modest associations between depression symptoms and infant sleep outcomes - Mathiasen Solvej; Parsons Christine E; Fusaroli Riccardo; Paavonen E Juulia; Karlsson Hasse; Karlsson Linnea (Elsevier BV, 2025)
Maternal depression and anxiety symptoms are common across the perinatal period and are associated with a raised risk for adverse child outcomes. While substantial evidence exists for child outcomes such as behaviour, language and cognition, infant sleep has been less studied. In this longitudinal study, we examined the association between maternal symptoms of depression and anxiety and mother-reported infant sleep at 6 and 12 months. Across the four infant sleep outcomes, total sleep time, sleep onset latency, number of awakenings and a maternal perception variable, we found modest effects for concomitant depression symptoms. There were almost no additional effects for anxiety symptoms beyond that already accounted for by depression. Using trajectory modelling of maternal symptoms at five time points, we found more robust effects for maternal groups with postnatally emerging symptoms over prenatally present symptoms across all four sleep outcomes. Our strongest finding was that mothers with postnatal depression symptoms were more likely to perceive their infant's sleep as problematic compared with all other mothers. Where we found effects on duration-based infant sleep outcomes overall, these were small and clearest for depressive symptoms over anxiety symptoms. For both nighttime awakenings and perception of sleep as a problem, effects were apparent only for mothers in the postnatal symptom groups, and not for prenatal symptoms, at both infant ages six and 12 months. Our sample was a relatively high-socioeconomic group with low symptoms overall, and findings may not generalize to more vulnerable populations.